Jérémie et la « coupe de la colère de Dieu » : une miniature inédite, premier jalon d’un discours anti-judaïque à Cluny au xe siècle - Laura Attardo (Bulletin du Centre d’Études Médiévales d’Auxerre)
Placed at the beginning of Raban Maur’s Commentary on Jeremiah – London, British Library, Add MS 22820, fol. 9ro –, the historiated initial of the prophet Jeremiah has never been studied. Produced under the abbatiate of Maieul (954-994), the image presents a unique iconographic formula whose several levels of interpretation allow us to understand the spirituality and ecclesiology of the community’s monks in the mid-to-late 10th century. Firstly, it provides precious evidence to the early anti-Judaic climate that developed at Cluny, culminating in the writings of the ninth abbot, Peter the Venerable (1122-1156). Placed in the context of its creation, the anti-Jewish discourse subsequently served as a basis for the development of a Cluniac ecclesiology focused on the redemption of sins.